Hubungan antara Ketuntasan Belajar Pendidikan Agama Islam dengan Kematangan Kognitif Siswa (Survei Pada Sekolah Menengah Pertama Negeri 02 Bekasi) - Desmawati Sri Ardi; Yayat Suharyat (Turats, 2011)
This research is to obtain empirical data from the proposed issue, namely to prove the existence of a positive relationship between "mastery learning study" Islamic Religious Education (PAI) "as a variable bound by the" student cognitive intelligence "as an independent variable. This study uses a survey method with correlation approach. From this research can be concluded that There is a correlation between learning completeness PAI (variable X) with cognitive maturity Junior High School students 02 Bekasi (Variable Y) obtained from linear regression calculation which produces a correlation coefficient of 0.34 and coefficient of determinant is 11, 56% and this means that there is a significant correlation between PAI learning completeness Students with Cognitive Maturity. So the higher the student learning completeness, the higher Student Cognitive Maturity. Cognitive maturity of students in learning greatly affects the learning process